Clonality, virulence genes, and antibiotic resistance of Staphylococcus aureus isolated from blood in Shandong, China - Wang, Xuezhi; Lin, Dongzi; Huang, Zengqi; Zhang, Jinmei; Xie, Wenyan; Liu, Pen; Jing, Huaiqi; Wang, Jiazheng (BMC microbiology, 2021)
Bloodstream infection (BSI) caused by Staphylococcus aureus (S. aureus) can be life-threatening and pose a great challenge to infection control and clinical treatment. However, little information exists regarding the characterization of S. aureus in BSI patients in Shandong, China. To identify the clonality, virulence genes, and antibiotic resistance of S. aureus in blood, a total of 101 nonrepetitive blood isolates were collected. The antibiotic resistance phenotypes were determined, and virulence genes were analyzed with polymerase chain reaction (PCR). Finally, the genetic relatedness was investigated with Staphylococcus chromosomal cassette mec (SCCmec) typing for methicillin-resistant S. aureus (MRSA) isolates, Staphylococcal protein A (spa), and multilocus sequence typing (MLST) for all of 101 isolates. Of the 101 S. aureus isolates, 24 MRSA isolates and 77 methicillin-susceptible S. aureus (MSSA) isolates were identified. Overall, MRSA isolates had higher resistance rates than MSSA isolates when exposed to any of the 15 antibiotics tested in this study except for trimethoprim/sulfamethoxazole. Among the 17 virulence genes tested in this study, hla, hld, and hlg could be detected in all isolates. MRSA isolates were more likely to carry seb and hlb genes, while MSSA isolates were more likely to carry seg and sei genes. Thirty-five sequence types (STs) and 49 spa types were identified, of which ST59-t437 and ST398-t571 were the most abundant. These two genotypes were also the most abundant ST-spa types in MRSA and MSSA isolates, but their abundances shifted over time, with ST398-t571 being the predominant genotype from 2016 to 2017, and ST59-t437 from 2018 to 2020. Besides, all the ST59-t437 isolates harbored hlgb gene, whereas most (88.9%) ST398-t571 did not. In addition, twenty-four MRSA isolates were subject to SCCmec typing. SCCmec IVa was the most prevalent SCCmec type, and all the ST59-t437 MRSA isolates were SCCmec IVa. We also observed 15 new STs, and some of them were MRSA. These findings provide additional observations and epidemiological data for blood S. aureus isolates, which can improve future infection-control measures and aid in potential clinical treatments in hospitals and other clinical settings.